Consolidation of amorphous powder by thermoplastic forming and subsequent mechanical testing. (15th February 2018) - Bochtler, Benedikt; Stolpe, Moritz; Reiplinger, Benedikt; Busch, Ralf
Abstract: Amorphous powder of the commercially available Zr-based glass-forming alloy AMZ4 (Zr59.3 Cu28.8 Al10.4 Nb1.5 ) is consolidated by thermoplastic forming (TPF). The glassy powder is heated into the supercooled liquid state, where its viscosity drops drastically and stress induced flow of the particles allows a binding of the powder sample. Here, we focus on the implementation of a TPF process on the way to an industrial production process. Various time and temperature protocols are tested and evaluated regarding the powder compaction and the conservation of the amorphous structure. Compact and amorphous samples are obtained and are subsequently tested by three-point beam bending. The results show that the consolidated samples are still outperformed by as-cast bulk material in bending, however reach the hardness of bulk material. The experimental observations in combination with isothermal crystallization times and equilibrium viscosity measurements in the supercooled liquid region allow to determine a generic TPF processing window that can be used as a predictive tool to assess the thermoplastic formability of different alloys. Graphical abstract: Image 1 Highlights: Amorphous Zr59.3 Cu28.8 Al10.4 Nb1.5 powder can be consolidated into dense and amorphous samples by thermoplastic forming (TPF) Consolidated powder samples reach the hardness of as-cast samples and one quarter of their strength under flexural load A generic process window for TPF can be defined by combining the time-temperature-transformation diagram with viscosity data